Comparative effectiveness of monotherapy vs. combination therapy for postoperative central nervous system infections in neurosurgical patients: a retrospective cohort study - Muyun Li; Wei Meng; Linna An; Xiaoqi Lin; Shangjie Yang; Qiang Fu; Qiuxia Shi; Dongfeng Li; Jie Wang; Jianhua Wang; Yubo Wang (BMC Infectious Diseases)
Abstract Background Although clinical guidelines recommend vancomycin-based combination therapy for patients with postoperative intracranial infections in neurosurgery, the trend of global bacterial resistance and the management of antimicrobial agents have made monotherapy a common treatment option for some patients. This study aims to compare the efficacy of single-drug therapy (SDT) versus vancomycin combination therapy (VCT) in treating central nervous system infections (CNSIs) following neurosurgery. Methods A retrospective cohort study was conducted, adjusting for various covariates such as length of stay (LoS), admission status, age, comorbidity status (Charlson Comorbidity Index, CCI), surgical and incision levels, and duration of surgery (DOS) using propensity score matching (PSM) with a 1:2 ratio. The treatment effects of the two empirical treatment regimens were evaluated through PSM and logistic regression for dual robustness. Results A total of 539 patients met the inclusion criteria, with 177 cases in SDT and 101 cases in VCT after PSM. The clinical cure rate was 76% in the SDT compared to 90% in the VCT (p = 0.007) after PSM. Of the result of antibiotic susceptibility testing, only 13.9% of cases identified specific pathogens, of which gram-positive cocci were the dominant. VCT was significantly more effective than SDT, both in unadjusted (OR 2.941, 95% CI 1.434–6.607, p = 0.005) and adjusted models (OR 3.605, 95% CI 1.611–8.812, p = 0.003). Gender, race, and surgical complexity were significant factors influencing treatment choice; female patients and those with complex surgeries were less likely to receive SDT. Although SDT was practically effective for treating CNSIs, VCT proved superior for complex infections. Conclusion The findings of this study suggest that, given concerns about antibiotic resistance and the varying complexities of infections, while SDT is effective in certain cases, VCT remains the preferred choice for complex CNSIs. This research provides important references for clinical practice, highlighting the need to consider multiple factors when selecting treatment options and advancing the understanding of treatment strategies for postoperative central nervous system infections.